The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1017/s1355617720000363
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Telomere Length Is Unrelated to Cognitive Performance Among Non-Demented and Demented Persons: An Examination of Long Life Family Study Participants

Abstract: Objective: Leukocyte telomere length (LTL) is a widely hypothesized biomarker of biological aging. Persons with shorter LTL may have a greater likelihood of developing dementia. We investigate whether LTL is associated with cognitive function, differently for individuals without cognitive impairment versus individuals with dementia or incipient dementia. Method: Enrolled subjects belong to the Long Life Family Study (LLFS), a multi-generational cohort study, where enrollment was predicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The flow chart of the selection process was exhibited in Figure 1. In total, 25 articles met our inclusion criteria 3–19,22–29. Among these studies, 22 articles were on the study of TL, 1 article was on the study of telomerase activity, and the remaining 2 articles focused on TL and telomerase activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The flow chart of the selection process was exhibited in Figure 1. In total, 25 articles met our inclusion criteria 3–19,22–29. Among these studies, 22 articles were on the study of TL, 1 article was on the study of telomerase activity, and the remaining 2 articles focused on TL and telomerase activity.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 25 articles met our inclusion criteria. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][22][23][24][25][26][27][28][29] Among these studies, 22 articles were on the study of TL, 1 article was on the study of telomerase activity, and the remaining 2 articles focused on TL and telomerase activity. Besides, Thomas et al 19 studied the TL of white blood cells, buccal cells, and brain tissue in AD patients and the matched controls, and the AD patients were divided into young and old AD groups, respectively.…”
Section: Research Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study has reported no correlation between telomere length and cognitive performance among non-demented and demented people in long-life family study participants. 36 It has also been reported that telomere length is not predictive of dementia or MCI conversion in the oldest old. 37 One study has shown that both longer telomere length and shorter telomere length are associated with an increased risk of AD in the Rotterdam study.…”
Section: Telomere Length In Neurodedenerative Disordersmentioning
confidence: 99%
“…Nonetheless, one large prospective study comprising n = 1,961 Dutch participants reported an U-shaped association, with higher risks of Alzheimer’s disease in the lowest and highest tertiles of TL relative to the middle tertile 28 . While, another cross sectional study comprising n = 2,210 participants demonstrating exceptional longevity from USA and Denmark reported null associations between leucocyte TL and cognitive performance in both cognitively unimpaired and demented sub-groups 29 .…”
Section: Introductionmentioning
confidence: 96%